Second generation Car-Parrinello molecular dynamics - Kühne, Thomas D. (Wiley Interdisciplinary Reviews: Computational Molecular Science, 2014)
Computer simulation methods, such as Monte Carlo or molecular dynamics, are very powerful theoretical techniques to provide detailed and essentially exact informations on rather complex classical many-body problems. With the advent of ab initio molecular dynamics (AIMD), where finite-temperature dynamical trajectories are generated using interatomic forces which are calculated on the fly using accurate electronic structure calculations, the scope of computational research has been greatly extended. This review is intended to outline the basic principles as well as being a survey of the field. Beginning with the derivation of Born-Oppenheimer molecular dynamics, the Car-Parrinello method and the recently devised Car-Parrinello-like approach to Born-Oppenheimer molecular dynamics, which unifies the best of both schemes are discussed. The predictive power of the latter second-generation Car-Parrinello molecular dynamics approach is demonstrated by several applications ranging from liquid metals to semiconductors and water. This development allows for ab initio simulations on much larger length and timescales than previously thought feasible. © 2013 John Wiley & Sons, Ltd.
CRIS-Team Scopus Importer:2023-03-20